An Experimental Study of the Effect of Tubercle Leading Edge on the Performance of NACA Airfoils - Moya Sanz, Carlos María (2018)
This thesis presents a study on tubercle leading edge configurations inspired in the Humpback Whale flipper. Is expected that stall appears at a higher angle of attack in a modified wing than in an unmodified wing. First a literature review is done and based on this review, 3 different configurations of wings are selected, varying between them the amplitude and wavelength of the tubercles. In order to perform this analysis an installation for measurement of forces is designed and built, together with the 3 modified wings and the unmodified one. The experiments are performed in a wind tunnel at Re=8.2x105. To support the results obtained in the tunnel, a simulation of the modified NACA 0012 with the best behavior is performed in SimScale, a CFD platform. From the experiments is obtained that wings which have tubercle leading edge, present better aerodynamics behavior in the post stall region, because for the three configurations, is seen that stall appears later and softer than the unmodified NACA 0012. Comparing the models is seen that the one which presents the smoothest stall is the wing with the smallest size of tubercles. That modified wing is analyzed in SimScale obtaining again a delay in stall in comparison with the unmodified NACA 0012. In terms of efficiency is seen that tubercles penalize the pre stall region, in return, post stall region presents better values of efficiency, being in that case the wing with medium size of tubercles the one with best aerodynamic efficiency performance. Finally, thanks to the results and conclusions obtained, the installation is validated. Ingeniería Aeroespacial